Stereotactic radiosurgery for essential tremor: Retrospective analysis of a 19‐year experience. Issue 5 (20th March 2017) - Niranjan, Ajay; Raju, Sudesh S.; Kooshkabadi, Ali; Monaco, Edward; Flickinger, John C.; Lunsford, L. Dade
ABSTRACT: Background : Essential Tremor (ET) is a common movement disorder that can be disabling. Initial treatment is in the form of medical therapies. Patients with medically refractory ET seek surgical intervention which include radiofrequency thalamotomy, deep brain stimulation, and radiosurgical thalamotomy. Radiosurgical thalamotomy is a minimally invasive surgical option which is especially valuable for elderly and high surgical risk patients. Objective : The purpose of this study was to retrospectively analyze the outcomes of stereotactic radiosurgery for patients suffering from medically refractory essential tremor. Methods : During a 19‐year period (1996–2015), 73 patients underwent gamma knife thalamotomy for intractable essential tremor. A median central dose of 140 Gy (range, 130–150) was delivered to the nucleus ventralis intermedius through a single 4‐mm isocenter. We used the Fahn‐Tolosa‐Marin clinical tremor rating scale to score tremor, handwriting, drawing, and ability to drink fluids. The median time to last follow‐up was 28 months (range, 6–152). Results : After gamma knife thalamotomy, 93.2% improved in tremor. Forty‐four patients (60.3%) experienced tremor arrest or barely perceptible tremor. Eighteen patients (24.7%) noted tremor arrest and complete restoration of motor function. Tremor improvement was sustained at last follow‐up in 96% of patients who experience tremor relief. Mean tremor score improved from 3.19 before to 1.27 after gamma knife thalamotomy ( P < 0.0001). Mean handwriting score improved from 2.97 to 1.25 ( P < 0.0001). Mean drawing score improved from 3.16 to 1.26 ( P < 0.0001). Mean drinking score improved from 3.14 to 1.56 ( P < 0.0001). Imaging follow‐up showed three types of lesions: enhancing lesion, streaking along internal capsule on fluid‐attenuated inversion recovery, and significant reactive changes. Three patients (4%) experienced temporary adverse radiation effects. Conclusion : Radiosurgery is a safe and valuable treatment option for medically refractory essential tremor, especially for the elderly or those with high surgical risk for DBS or radiofrequency thalamotomy. © 2017 International Parkinson and Movement Disorder Society